2014
DOI: 10.1039/c4tc00543k
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon excited fluorescence of BF2complexes of curcumin analogues: toward NIR-to-NIR fluorescent organic nanoparticles

Abstract: Two-photon excitation of curcuminoid borondifluoride nanoparticles in water results in rather efficient luminescence in the near infrared region due to a high two-photon cross-section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 73 publications
4
62
0
Order By: Relevance
“…Subsequently Tomapatanaget et al [22] presented a detailed photophysical study for the curcumin boron complexes and also the cyanide detection ability of the difluoroboron curcumin analogs in aqueous media. In past few years novel difluoroboron analogs of curcumin with different donor groups conjugated to the difluoroboron enolate were reported [24][25][26][27] showing that the different structural modification well contributed in enhancement of the chemical and photophysical properties of these class of molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently Tomapatanaget et al [22] presented a detailed photophysical study for the curcumin boron complexes and also the cyanide detection ability of the difluoroboron curcumin analogs in aqueous media. In past few years novel difluoroboron analogs of curcumin with different donor groups conjugated to the difluoroboron enolate were reported [24][25][26][27] showing that the different structural modification well contributed in enhancement of the chemical and photophysical properties of these class of molecules.…”
Section: Introductionmentioning
confidence: 99%
“…26 Owing to their extended p-conjugated structure, their borondiuoride complexes exhibit strong visible absorption and uores-cence, [27][28][29][30][31][32][33] and unique near-infrared (NIR) emission in both solution and in the solid state using one-and two-photon excitation. 34,35 As a result of these features, they are attractive molecules for bioimaging and virtually any application requiring highly absorbing and emitting materials such as organic photovoltaics and optoelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent studies, [32][33][34][35] we showed that the unique linear and nonlinear optical properties of borondiuoride complexes of curcuminoids also stem from the combination of electron donor (D) and acceptor (A) units in a D-A-D quadrupolar-like architecture in which A is the central dioxaborine ring and D is a terminal aromatic moiety acting as an electron donor substituent. As such, these compounds are highly solvatochromic dyes and their emission wavelengths can be tuned over the entire visible spectrum up to NIR region by controlling the strength of the terminal donor group.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of BF2 complexes of 2'-hydroxychalcones and curcuminoids, we showed that NIR emission property is characteristic of tightly packed chromophores experiencing strong excitonic coupling. [3,12] A similar behavior has been reported to account for "excited multimer" fluorescence in stacks of diaroylmethanoboron difluoride molecules built on π-orbital overlap between benzene and dioxaborine rings. [13] Therefore, the solid-state optical signature of difluoroboron β-diketonate dyes is generally strongly sensitive to supramolecular packing.…”
Section: Introductionmentioning
confidence: 77%